PENGEMBANGAN PAKAR IPS (PAPAN KARAMBOL IPS) SEBAGAI MEDIA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Maryanti, Rani Dwi; Qurrotaini, Lativa (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
The background of this research is the implementation of a very minimal educational game tool and students are less attentive to the teacher's explanation during the learning process. So it affects the value of low students. This research aims to develop the instrument of Educational games Carrom Board IPS (EXPERTS IPS) on the subject of IPS materials economic activity and natural Resources class IV Elementary School and know the feasibility of the use of educational game tools of the EXPERT IPS. The research was conducted at the state Elementary School in Bekasi Regency with research subjects amounting to 8 students of IV A class. The type of research used is Research and Development (RD). The development procedures used to refer to ADDIE's research and development model. The instruments used are observation and poll. The IPS EXPERT has been through the revision stage based on suggestions and input from 3 validators. The results showed that the resulting IPS EXPERTS deserves to be used as an educational tool game material of economic and natural resources in grade IV Elementary School. This is based on the results of expert validation of material with an average percentage of 97% Belong to a very decent quality category. The validation result of media experts with an average percentage of 93% which belongs to the category of quality is decent. Trials by students with an average percentage of 96% which belongs to the category of quality are decent. Conclusion: has been developed the educational game tools of the EXPERT IPS IPS and is worthy to be used as an educational tool in elementary school with an increase in the value of learning results of the average student IPS of 81.Keywords: papan karambol IPS; educative game; economic activity and natural resources